Long-term remission of intractable systemic vasculitis with monoclonal antibody therapy. - Lockwood, C; Thiru, S; Isaacs, J; Hale, G; Waldmann, H (1993)
Monoclonal antibodies that target T cells offer an alternative to conventional immunosuppressive drugs in the management of autoimmune disease. "Humanisation" of such monoclonal antibodies makes their clinical use less likely to be prone to the risk of cross-species sensitisation than treatment with rodent antibodies. We describe humanised monoclonal antibody therapy in four patients with severe systemic vasculitis unresponsive to immunosuppressive drugs. Substantial and sustained benefit was seen in three of the four patients, although one of these three patients developed anti-idiotypic antibodies that had to be removed by plasma exchange.